Wizerunek III RP w dyskursie o. Tadeusza Rydzyka w kontekście „walki o multipleks” - Przybysz, Kinga (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The subject of this paper is the discourse of Tadeusz Rydzyk – the director of Radio Maria. Author analyzes priest’s statements in order to see his view of Poland. Three context of discourse are taken into consideration: political, economical and medial. Author analyzes also rhetorical and language tools used by Tadeusz Rydzyk. Findings suggest that T. Rydzyk depicts Poland as undemocratic state in which Catholics are discriminated.